TEXT – ART FOR LISTENERS - Gagoshidze, Tamar (European Scientific Journal, ESJ, 2014)
Since the last century, the text is understood as a poly-semiotic structure. For example, P. Sergio, based on French experience, offers the list 136comprising eight formed components; that is the idea of “discourse” in the text related to theory is already ambiguous. We can identify three main determinants of “discourse” based on different cultures and thoughts. In the linguistic context, the term was first coined by American scientist Z. Harris in his article “Discourse Analysis137”. However, the broad application of the term was acquired twenty years later. In the world of linguistics, discourse is defined as a speech, text, dialogue, which is an integral part of communicational case. Thus, discourse is countering the text both dynamically and statically. The understanding of the term by French Structuralists and Post-Structuralists is indicated through works by M. Foucault 138and his followers. According to the scientists, discourse equates the style of speech, the manner and carries individualistic qualities (political discourse, teachers’ discourse, the authors’ style as discourse). This vision represents discourse in a social color.